Bi-Directional Communication Between Neurons and Astrocytes Modulates Spinal Motor Circuits - Broadhead, Matthew J.; Miles, Gareth B. (Frontiers in Cellular Neuroscience, 2020)
Growing evidence suggests that astrocytes are not merely supportive cells in the nervous system but may actively participate in the control of neural circuits underlying cognition and behaviour. In this study, we examined the role of astrocytes within motor circuitry of the mammalian spinal cord. Pharmacogenetic manipulation of astrocytic activity in isolated spinal cord preparations obtained from neonatal mice revealed astrocyte-derived, adenosinergic modulation of the frequency of rhythmic output generated by the locomotor central pattern generator network. Live Ca2+ imaging demonstrated increased activity in astrocytes during locomotor-related output and in response to direct simulation of spinal neurons. Finally, astrocytes were found to respond to neuronally-derived glutamate in an mGluR5 dependent manner, which in turn drives astrocytic modulation of the locomotor network. Our work identifies bi-directional signalling mechanisms between neurons and astrocytes underlying modulatory feedback control of motor circuits, which may act to constrain network output within optimal ranges for movement.